Polycyclic aromatic hydrocarbons in urban soils of Beijing: Status, sources, distribution and potential risk - Peng, Chi; Chen, Weiping; Liao, Xiaolan; Wang, Meie; Ouyang, Zhiyun; Jiao, Wentao; Bai, Yang (Environmental pollution (1987), 2011)
We studied the source, concentration, spatial distribution and health risk of 16 polycyclic aromatic hydrocarbons (PAHs) in urban soils of Beijing. The total mass concentration of 16 PAHs ranged from 93 to 13 141 μg kg −1 with a mean of 1228 μg kg −1. The contour map of soil PAH concentrations showed that the industrial zone, the historical Hutong district and the university district of Beijing have significantly higher concentrations than those in remainder of the city. The results of sources identification suggested that the primary sources of PAHs were vehicle exhaust and coal combustion and the secondary source was the atmospheric deposition of long-range transported PAHs. The incremental lifetime cancer risks (ILCRs) of exposing to PAHs in the urban soils of Beijing for adult were 1.77 × 10 −6 and 2.48 × 10 −5, respectively under normal and extreme conditions. For child, they were 8.87 × 10 −7 and 6.72 × 10 −6, respectively under normal and extreme conditions. ► The primary sources of PAHs in Beijing soil were vehicle exhaust and coal combustion and the secondary source was the atmospheric deposition of long-range transported PAHs. ► Three areas of high PAH concentration soils are identified by Kriging interpolation included the industrial zone, the historical Hutong district and the university district. ► The estimated incremental lifetime cancer risks associated with exposing to soil PAHs in Beijing for both adults and children are acceptable. A systematic investigation demonstrates the sources, distribution and health risk in Beijing urban soil using mathematical, statistical and geostatistical methods.